Due Process and Federal Grant Termination: Challenging Agency Discretion Through a Reasons Requirement - Robert S. Catz (Washington University Law Quarterly, 1982)
This Article focuses on two potential sources of a grantee's right to some kind of hearing to review a federal agency's decision to terminate the grant relationship. The main objective is to demonstrate that the grantee has a property and/or liberty interest in the grant, which triggers procedural due process guarantees, and that the process due is notice of the possible deprivation of the grant and a pretermination hearing.
Keywords: Goldberg v. Kelly 397 U.S. 254 (1970); Administrative procedure; Due process of law; Grants-in-aid; Intergovernmental fiscal relations; United States